Hak Anak Angkat terhadap Harta Peninggalan Orang Tua Angkat menurut Hukum Islam - Susiana Susiana (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: An adopted child is the child which his rights has been changed from his parents, guardian that is valid or other people that are responsible for taking care, education and to grow the child by in the family of adopted parents based on the decision of the court. The parents are responsible for daily life and education of the child. In Islamic law the adopted parents are still having relationship with his biological parents; hence the child is not going to be one of the parties receiving the legacy from the adopted parents. If the parents die, the adopted child would not be one of them but Islamic law provide centanty and protection to the child receiving the legacy from his adopted parents is through the institution wasiat wajibah as ruled in Article 209 (2) of Islamic Law Compilation. The Rights of Adopted Child Towards the Inheritance of Adopted Parents Based on Islamic Law